The Proteocephalus Species-Aggregate in Freshwater Centrarchid and Percid Fishes of the Nearctic Region (North America) - Scholz, Tomáš; Choudhury, Anindo; Uhrová, Lucie; Brabec, Jan (The Journal of parasitology, 2019)
In the present paper, species of the Proteocephalus-aggregate de Chambrier, Zehnder, Vaucher, and Mariaux, 2004 (Cestoda: Proteocephalidae) reported from centrarchid and percid fishes in North America are reviewed, and their taxonomic status is critically assessed based on a study of type specimens and new material from Canada and the United States. The following 3 species, supposedly strictly specific to their fish definitive hosts, are recognized as valid: (1) Proteocephalus fluviatilis Bangham, 1925 (new synonyms Proteocephalus osburni Bangham, 1925 and Proteocephalus microcephalus Haderlie, 1953 ; Proteocephalus 'robustus' nomen nudum) from the smallmouth and largemouth bass, Micropterus dolomieu (Lacépède) (type host) and Micropterus salmoides (Lacépède) (both Centrarchidae); (2) Proteocephalus luciopercae Wardle, 1932 (new synonym Proteocephalus stizostethi Hunter and Bangham, 1933 ) from the walleye, Sander vitreus (Mitchill) (type host), and sauger, Sander canadensis (Griffith et Smith) (Percidae); and (3) Proteocephalus pearsei La Rue, 1919 , a parasite of the yellow perch, Perca flavescens Mitchill (Percidae). All species are illustrated based on new, properly heat-fixed material. Scanning electron micrographs of the scoleces of percid tapeworms P. luciopercae and P. pearsei, as well as the bass tapeworms P. fluviatilis and Proteocephalus ambloplitis ( Leidy, 1887 ), the latter of which does not belong to this Proteocephalus-aggregate, are provided for the first time together with a simple key to species identification of proteocephalids from centrarchiform and perciform teleost fishes.
Keywords: Animals; Cestoda; Perches; Kanada; Perciformes; okounovití; cestodózy; nemoci ryb; Fish Diseases; DNA, Helminth; Fresh Water; Phylogeny; Canada; Spojené státy americké; DNA helmintů; sladká voda; United States; Cestode Infections; zvířata; fylogeneze